2019
DOI: 10.1039/c9an00830f
|View full text |Cite
|
Sign up to set email alerts
|

Mannitol-induced gold nanoparticle aggregation for the ligand-free detection of viral particles

Abstract: Addition of osmolytes causes viruses-coated AuNPs to aggregate and not protein-coated AuNPs. Ligand-free detection of virus was developed without the need for prior knowledge of the specific virus target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…PPV was propagated in PK-13 cells, and BVDV was propagated in BT-1 cells, as described previously, 43,44 and stored at −80°C until further use. PPV or BVDV were further purified with a Biotech Cellulose Ester 1000 kDa dialysis tubing (Rancho Dominguez, CA) and a BioRad Econo-Pac 10DG desalting column (Hercules, CA) in PBS buffer, as previously described, 45 and stored at 4°C until further use.…”
Section: Virus Production Purification and Titrationmentioning
confidence: 99%
“…PPV was propagated in PK-13 cells, and BVDV was propagated in BT-1 cells, as described previously, 43,44 and stored at −80°C until further use. PPV or BVDV were further purified with a Biotech Cellulose Ester 1000 kDa dialysis tubing (Rancho Dominguez, CA) and a BioRad Econo-Pac 10DG desalting column (Hercules, CA) in PBS buffer, as previously described, 45 and stored at 4°C until further use.…”
Section: Virus Production Purification and Titrationmentioning
confidence: 99%
“…Previous studies have suggested a strong contribution of binding valency and biomarker size to inducing nanoparticle aggregation. 35,36 As EVs are multivalent targets with multiple surface biomolecules, we thus examined the effect of PMP size in inducing nanoparticle aggregation. We prepared different-sized PMPs and measured their aggregation when treating to an equal concentration of EVs and lectin RCA120 ( Figure 3A).…”
Section: Optimized Assay For Ev-bound Glycansmentioning
confidence: 99%
“…PPV and BVDV were purified using a previously established method with dialysis and a desalting column [24]. The buffer for purification was either phosphate-buffered saline (PBS) (pH 7.2) (for the hydrophobicity study) or 20 mM phosphate buffer (PB) (pH 7.0) (for the surface charge study).…”
Section: Virusmentioning
confidence: 99%